Determining the dynamics of electromagnetic fields, air ionization, low-frequency sound and their normalization in premises for computer equipment - Glyva, V; Kasatkina, N; Levchenko, L; Tykhenko, O; Nazarenko, V; Burdeina, N; Panova, O.; Bahrii, M.; Nikolaiev, K.; Biruk, Y. (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР", 2022)
Computers are an important technical tool in many types of administrative, production, and educational activities. They are the main tool in managing technological processes at industrial enterprises, in air traffic management, the generation and transmission of electricity, etc. Users of this category perform responsible work, the quality and infallibility affect the safetyof people, the smooth operation of enterprises, and the quality of products. Therefore, such personnel must be provided with the most favorable working conditions. Significant impact on workers is exerted by such physical factors of the production environment as microclimate, electromagnetic fields, insufficient air ionization, noise.
Keywords: personal computer; physical factors; microclimate; electromagnetic field; air ionization; infrasound; 628.8